The academic self-efficacy among students who took the K+12 curriculum and the revised basic education curriculum - Bacalso, John Michael P. 4 0 16; 5 (2019)
ABSTRACT: The research was entitled The Academic Self-Efficacy of Students of Pamantasan ng Maynila Who Took The K+12 Curriculum and The Revised Basic Education Curriculum. This study aimed to determine how the implementation of the K+12 educational program, and the educational program prior to it, in the Philippines affected the sense of academic self-efficacy of college undergraduates in Pamantasan ng Lungsod ng Maynila (PLM). The participants of the study were bonafide students of PLM and were either products of the K+12 program or Revised Basic Education Curriculum. The researcher administered a 33-item scale, College Academic Self-Efficacy Scale (Owen & Froman, 1988), through paper and pen. Their demographic profiles weren't considered as variables of the study. The researcher found that the academic self-efficacy of students from both groups were at moderate level and there was no significant difference between the mean scores of the respondents. The researcher attributed the result to some factors like the maturity of the participants.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2